Online Buying And Selling In The Pre-Order System From An Islamic Legal Perspective - Ahmad Nizar Mohammad Syamwil; Mhd Soleh Hasibuan (AT-TAFAHUM: Journal of Law, 2021)
Online buying and selling using a pre-order system is a modern form of transaction in muamalah activities that has developed along with advances in digital technology. This system allows buyers to place orders and pay in advance, while the goods are delivered at a later date according to the agreement between the seller and buyer. From an Islamic legal perspective, this practice bears similarities to the salam contract, which is a transaction involving advance payment and future delivery of goods. This study aims to analyze the pre-order buying and selling mechanism and assess its compliance with Sharia principles. The results indicate that pre-order transactions are essentially permissible as long as they meet the pillars and conditions of the contract, such as clarity of the goods, price, delivery time, and a clear agreement between the two parties. However, this practice also has the potential to pose risks such as unclear goods, delayed delivery, and elements of gharar (unclear risk), which can harm one of the parties. Therefore, the principles of transparency, honesty, and responsibility are required in its implementation to comply with the values of justice in Islamic law.